Replication Data for: Priority regions for research on dryland cereals and legumes - Barona, Elizabeth; Guevara, Edward D.; Hyman, Glenn G. (2016)
This data set characterizes dryland systems and cereal and legume crops (Hyman et al., 2016). The data is a subset of a larger data set that characterizes the farming systems of John Dixon’s global farming systems framework and map (Dixon et al., 2001; Barona and Hyman, 2016). The data subset focuses on the following crops: chickpea, common bean, cowpea, faba bean, groundnut, lentils, pigeon pea, soybean, barley, pearl millet, small millet and sorghum. The geographic unit of analysis is a combination of 63 farming systems and 250 countries, for a total of 544 spatial units. For each of these units, data has been compiled on crop area, crop yield, crop production, population, poverty, drought, heat, soil conditions and other information.